The Severity Factor Of Injury Risk In Tennis Athletes - Budi, Didik Rilastiyo; Deri Listiandi, Arfin; Kusnandar; Joko Nurcahyo, Panuwun (Journal of Physical and Outdoor Education, 2023)
Body composition and shape according to ideal Body Mass Index (BMI) conditions are crucial factors for tennis athletes to reach high performance and avoid the risk of injury. This study aimed to determine the correlation between Body Mass Index (BMI) and the injury rate in tennis athletes in Banyumas Regency. The research instrument used a body mass index (BMI) and Functional measurement test. The measurement profile is strengthened by the athlete's injury archives data using an injury questionnaire. The research method uses the Correlational method. Data analysis used normality test, linearity test, and correlation test to comprehend the level of relevance between Body Mass Index (BMI) and the prevalence of injury in tennis athletes. Identification of Body Mass Index (BMI) and risk of injury in tennis athletes is essential for coaches to design an accurate training program for athletes to achieve high performance during training and competitions. The results showed that the significance value was 0.000 or stated a relationship or relevance between BMI and the risk of injury in tennis athletes. BMI results show that the average BMI is in normal conditions (22.36), and FMS results for the risk of injury to tennis athletes are in the category of having a low risk of injury. The results of this study provide information about the importance of the ideal composition of Body Mass Index (BMI) to avoid the possibility of sports injuries caused by excessive body weight. Identification of Body Mass Index (BMI) and risk of injury in tennis athletes is essential information for coaches to design the right training program for athletes to achieve high performance during training and matches